Staged surgery for closed Lisfranc injury with dislocation - He, Wenbao; Xia, Jiang; Zhou, Haichao; Li, Zhendong; Zhao, Youguang; Yang, Yunfeng; Li, Bing (Frontiers in Surgery, 2022)
Objective To investigate the clinical efficacy of staged surgery for patients with closed Lisfranc injury and dislocation. Methods This study included 48 patients with acute closed Lisfranc injury and dislocation admitted between July 2016 and July 2021. The patients were divided into two groups. 23 patients in group A underwent staged surgeries included emergency reduction within 4–8 h after injury, and open reduction and internal fixation of Lisfranc injury and first tarsometatarsal joint fusion after the swelling had subsided. 25 patients in group B underwent open reduction and internal fixation as an elective procedure after the swelling had subsided. American Orthopedic Foot and Ankle Society (AOFAS) midfoot scores and visual analog scale (VAS) scores were used for assessment at the final follow-up. Results A total of 48 patients with closed Lisfranc injury and dislocation were included. The lengths of hospitalization were 11.52±1.61 d and 19.80±2.37 d in groups A and B, respectively. The total lengths of surgery were 67.34±1.71 min and 104.36±8.31 min in groups A and B, respectively. 48 patients completed the final follow-up (follow-up period range: 2–24 months, mean: 18 months). All fractures had healed at 12–18 weeks after surgery (mean: 14.6 weeks). At the 1-year postoperative follow-up, the AOFAS and VAS score was 86.87±4.24 and 1.91±0.78, respectively, during weight-bearing walking in group A patients and 71.72±5.46 and 3.20±1.17 in group B. By the end of the follow-up period, only 2 patients in group B had developed traumatic arthritis and no patients had joint re-dislocation or required secondary surgery. Conclusion Staged surgery for closed Lisfranc injury with dislocation reduced the incidence of perioperative complications and achieved good surgical outcomes while shortening the lengths of surgery and hospitalization.